Base‐amplifying silicone resins with photobase‐generating side chains and their application to negative‐working photoresists. Issue 10 (21st February 2015) - Furutani, Masahiro; Kobayashi, Hiroshi; Gunji, Takahiro; Abe, Yoshimoto; Arimitsu, Koji
ABSTRACT To accomplish high photosensitivity of resist systems including photobase generators, we have proposed the concept of base‐proliferation reactions that generate base molecules in a nonlinear manner by the action of a catalytic amount of base; however, excessive diffusion of generated base molecules is still a problem. We have designed novel functional silicone resins bearing both base‐amplifying units and photobase‐generating units, and synthesized resins with various composition ratios. The synthesized resins are decomposed autocatalytically after UV irradiation and subsequent heating at 100 °C, which indicates progression of base‐proliferation reactions. High photosensitivity (8.1 mJ cm−2) was recorded, and it was found that the photosensitivity is about 490 times enhanced by replacing a base‐catalytic reaction system with the base‐proliferation reaction system. Furthermore, a 4 × 10 µm line‐and‐space pattern has been successfully fabricated using the silicone resin. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 1205–1212